Tracking women and children in a Continuum of Reproductive, Maternal, Newborn, and Child Healthcare (RMNCH) in India - Rajesh Kumar Rai (Springer, 2019)
The Continuum of Reproductive, Maternal, Newborn, and Child Healthcare (RMNCH) model is suggested to be an effective tool to improve maternal and child health. This short dispatch proposes that if India pursues the continuum of care model, a well-designed follow-up strategy to track prospective mothers and their children is imperative.